Designing an Ethical Leadership Model for Managers of Educational Organizations (Case Study: Educational Organizations in Tehran Province) - Kazemi Loyeh, Firouz; Kamali, Naghi; Mojtaba Zadeh, Mohammad (Future of Work and Digital Management Journal, 2025)
Today, ethical leadership in organizations has received considerable attention and is rapidly expanding because the moral failures of managers across organizations, environments, and sectors have drawn attention to the importance of ethical leadership. Ethical leadership can be considered a point of convergence between spiritual leadership and transformational leadership. What is significant in ethical leadership is that ethical leaders think about the outcomes, consequences, shortcomings, and benefits of the decisions they make in the long term. In every organization, ethical leaders are the center and pivot of high moral standards and act in alignment with these standards to guide their conduct. Ethical leaders also make the behavioral boundaries within the organization clear and explicit to employees. The main objective of the present research was to design a desirable ethical leadership model for managers of educational organizations in Iran. Accordingly, this study employed a qualitative approach based on the grounded theory method. Within this method, the systematic approach (Straussian approach) was used to derive the paradigm model. In the quantitative phase, the current state of ethical leadership was examined. This research was applied in purpose and used an exploratory mixed-method design (combining qualitative and quantitative approaches). In the quantitative phase, because the current situation was assessed, a descriptive survey method was used, while in the qualitative phase, the study explored and examined concepts and categories related to the dimensions of the desirable ethical leadership model for managers of Iranian educational organizations using MAXQDA software. The statistical population consisted of managers of educational organizations in Tehran. Using Cochran’s formula, a sample of 252 managers was selected through purposive and snowball sampling methods. The results of the model fit analysis using AMOS and PLS software indicated that the proposed structural model had a good fit. Furthermore, it was found that among the conditional factors, only contextual and intervening factors had a significant direct effect on interactive factors, while causal factors did not have a significant effect on interactive factors. Additionally, the indirect effect of causal factors on consequential factors was not significant, but the indirect effect of intervening and contextual factors on consequential factors was significant.